Prevalence of hepatitis E virus antibodies in children in Germany - Krumbholz, Andi; Schroten, Horst; Tenenbaum, Tobias (The pediatric infectious disease journal, 2014)
Background: Since asymptomatic hepatitis E virus (HEV) infections particularly affect children, there is a need for studies to determine the HEV seroprevalence among infants, children and adolescents. Methods: The prevalence of anti-HEV IgG antibodies was determined in sera taken in 2008-2010 from 1646 children aged 0-17 years living in Germany. Antibody testing was carried out using the enzyme-linked immunosorbent assay recomWell HEV IgG as well as the recomLine HEV IgG/IgM distributed by Mikrogen. Furthermore, the performance of MP Biomedicals enzyme-linked immunosorbent assay HEV and the HEV-Ab enzyme-linked immunosorbent assay from Axiom was analyzed in comparison with the recomWell/recomLine test system using a defined subset of sera. Results: In children, the overall prevalence of antibodies was 1.0%. Starting with the 5- to 6-year olds, there was a significant increase of HEV seroprevalence to 1.5% in the group of the 15- to 17-year olds. There was no statistically significant difference between seroprevalences of boys (1.2%) and girls (0.7%). Passively transmitted maternal antibodies persisted for about 3 months. The strength of agreement between the recomWell/recomLine system and the ELISAs from MP Biomedicals or Axiom varied between 0.229 and 0.542 and was calculated at 0.111 when the assays from MP Biomedicals and Axiom were compared. Conclusions: In Germany, only a very small number of HEV infections occur in children. Many infections occur in adults with increasing age. Because of considerable variations in assay accordance, there is an urgent need for standardization of HEV serology.